Progression of Inflammatory Bowel Diseases Throughout Latin America and the Caribbean: A Systematic Review - Kotze, Paulo Gustavo; Underwood, Fox E.; Damião, Aderson Omar Mourão Cintra; Ferraz, Jose Geraldo P.; Saad-Hossne, Rogerio [UNESP]; Toro, Martin; Iade, Beatriz; Bosques-Padilla, Francisco; Teixeira, Fábio Vieira; Juliao-Banos, Fabian; Simian, Daniela; Ghosh, Subrata; et al. (Elsevier, 2020)
Background & Aims: The incidence of inflammatory bowel diseases (IBD) is increasing in Latin America. We performed a systematic review to identify clinical and epidemiologic features of IBD in Latin America (including Mexico, Central America, and South America) and the Caribbean. Methods: We searched MEDLINE, EMBASE, and SciELO databases for clinical or epidemiologic studies of Crohn's disease (CD) or ulcerative colitis (UC) from Latin American and Caribbean countries and territories that reported incidence, prevalence, ratio of UC:CD, IBD phenotype, and treatment, through September 12, 2018. Data were extracted from 61 articles for analysis. Results: The incidence and prevalence of IBD have been steadily increasing in Latin America and the Caribbean. The incidence of CD in Brazil increased from 0.08 per 100,000 person-years in 1988 to 0.68 per 100,000 person-years in 1991–1995 to 5.5 per 100,000 person-years in 2015. The highest reported prevalence of IBD was in Argentina, in 2007, at 15 and 82 per 100,000 person-years for CD and UC, respectively. The ratio of UC:CD exceeded 1 in all regions throughout Latin America and the Caribbean with the exception of Brazil. Treatment with tumor necrosis factor antagonists increased steadily for patients with CD (43.4% of all patients in Brazil were treated in 2014) but less so for patients with UC (4.5% of all patients were treated in 2014). Surgery for IBD decreased with time. In Chile, surgeries were performed on 57.0% of patients with CD and 18.0% of patients with UC during the period of 1990–2002; these values decreased to 38.0% and 5.0%, respectively, during the period of 2012–2015. In Peru, 6.9% of patients with UC received colectomies in the period of 2001–2003 and 6.2% in 2004–2014. Conclusions: In a systematic review, we found the incidence of IBD to be increasing throughout Latin America and the Caribbean. Population-based epidemiology studies are needed to evaluate the increase in IBD in these regions, which differ from other global regions in climate, culture, demographics, diet, healthcare delivery and infrastructure, and socioeconomic status.
Keywords: Anti-TNF; Ethnicity; Incidence; Inflammatory Bowel Disease; Prevalence; Race; Risk Factor